Segmentación del mercado por motivaciones bajo una oferta emprendedora para el turismo en el Cantón Portoviejo - Hidalgo Zambrano, Cindy Paola (2023)
The present work had as a general objective the segmentation of tourists in relation to the market under an entrepreneurial offer that contributes to tourism in Portoviejo canton. The first phase of the study proposed the development of a diagnosis through bibliographic review, search of official documents, field visits, surveys and interviews, to know the current state of the destination in the environmental, socioeconomic and tourist fields, likewise, to have an overview range of enterprises that contribute to tourism. In the second phase, through surveys, interviews and the use of statistical analysis, the tourist demand was characterized, determining the behavior and motivations of the visitors, which in the third phase allowed a detailed segmentation to be carried out, as well as establishing the existing differences in the respective clusters, through the correlation and regression of variables in the SPSS software. The study identified three profiles of tourists, who move according to the following motivations: gastronomic culture; nature, ecotourism and sun and beach.